Pengaruh Metode Group Investigation terhadap Hasil Belajar Siswa pada Muatan Materi PPKn di Kelas V SDN 2 Kalijaga - Zuhdi, Ferianto; Khairunnisa, Khairunnisa; Syahrul Jiwandono, Ilham (ZAHRA: Research and Tought Elementary School of Islam Journal, 2021)
One of the factors that impact the unsuccessfulness of studying PPKn in schools is the use of a learning model that is still less innovative. Teachers tend to use the old method that is teaching the materials using lectures, questions and answers, then giving the student assignments. As a result, students feel bored, passive, less interested in learning, which decrease students’ learning outcomes. Group Investigation can be used as an alternative that will encourage students to be more active in learning with groups. This study aims to determine the effect of Group Investigation on students’ learning outcomes in studying PPKn in the fifth grade student at SDN 2 Kalijaga academic year 2020/2021. This research is experimental research with Quasi Experimental Design type Nonequivalent Control Group Design. Population of this research was the fifth grade students of SDN 2 Kalijaga in academic year 2020/2021 consisting of two classes. The total number of the population was 45 people, all of them were chosen as the sample, where V/A as the experimental class and V/B as the control class. The researcher conducted observation and test to collect the required data. The result from the observation of applying Group Investigation in teaching indicate "fantastic" category with an percentage of 93.18% at the first meeting and 95.45% at the second meeting. The results showed that the score of student learning outcomes after being given treatment using Group Investigation was higher than before treatment. This is indicated by their pre-test score that is 50. After being given treatment their score increased become 86.81 in the post-test. Based on the results of hypothesis testing of independent samples t test using SPSS 16.0 showed that the value of tcount equal to (2.742 and 2.727) > ttable (0.294) for students’ achievement and significance level signify (Sig. 2-tailed) 0.009 < 0.05. So that, it can be concluded that H0 is rejected and Ha is accepted. It means that there is a positive effect of Group Investigation on the students’ learning outcomes in studying PPKn at grade V students of SDN 2 Kalijaga in the academic year 2020/2021.